The Study of Verbal Exegesis by Tuan Guru Hasanain on the Environment - Zulkarnaen; Idil Hamzah (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2024)
This article will discuss fiqh al-bi’ah as an offer of Islamic concepts against the ecological crisis. Global societies today face environmental crises, global warming, climate change, droughts, and other ecological problems. Conscious or not, humans are the main perpetrators of the destruction of the living environment by exploiting natural resources. This paper is intended to find a way out of the ecological crisis through the approach of the Fiqh al-bi’ah paradigm. It is especially important for Muslims to have a legal foundation that can serve as a foundation for thinking and acting in dealing with environmental issues. This writing is a library study whose data is obtained from some literature in particular that offends the environmental issues of living. More specifically, this research will use the maslahat approach in the theory of Islamic law. To deepen his study, the article will also look at the classic and contemporary fiqh paradigms. As the findings of the article show, it turns out there are quite significant differences between the paradigms of the classic fiqh concepts and the contemporary-related fiqh al-bi'ah. Through this article, I argued that keeping the environment could be considered one of the Maqasid al- Syari'ah.